PENGARUH SENGKETA BATAS WILAYAH ANTARA INDONESIA DAN MALAYSIA DI PULAU SEBATIK TERHADAP KEHIDUPAN SOSIAL EKONOMI - Vika Senia; Tsaniya Zahrah Permana (Universitas Negeri Padang, 2023)
Many boundary disputes are caused by many factors, therefore boundary arrangement is very important to do. Sebatik Island is one of the small islands of tens of thousands of islands owned by the Indonesian state. Sebatik Island is divided into two parts, one part of the northern island goes into Malaysian territory, and the other part is the southen part into Indonesian territory. Because this island is the border of the country, the location of Sebatik is very strategic for both countries and makes Sebatik Island prone to conflict. In conducting research this Journal Article used is a mixed research method, which is a research method that combines two qualitative and quantitative research methods in a research activity.